Simulated Mitigation of Tsunami Disasters in the Coastal Area of Purworejo Regency, Central Java, Indonesia - Sudaryatno Sudaryatno; Josaphat Tetuko Sri Sumantyo; Taufik Heri Purwanto; Inti Raidah Hidayat; Maulida Allya Nasikha (Forum Geografi, 2022)
The coastal area of Purworejo Regency has the potential to be hit by a mega-tsunami disaster because it includes the southern coast of Java Island which is faced with seismic gaps that may produce large earthquakes in the future. This study aims to simulate tsunami disaster mitigation in the coastal area of Purworejo Regency in an effort to raise awareness and increase the community capacity for dealing with potential tsunamis so that the level of loss can be minimized. The tsunami risk analysis is based on the Disaster Crunch model, which is a combination of vulnerability analysis based on the weighted overlay quantitative method and tsunami hazard analysis based on tsunami inundation reduction modeling and cost distance analysis. The planning of the tsunami evacuation route is based on the network analysis method. The tsunami-risk area with a run-up scenario of three meters in the coastal area of Purworejo Regency 126,29 square kilometers or about 72,52% of the total coastal area. There are five tsunami evacuation plan points, with five main tsunami evacuation routes that lead directly to each of these points.